Estudio del Patrimonio Inmaterial del Ámbito uso Social, Rituales y Actos Festivos Subámbito fiestas Religiosas de la Comunidad Papahurco del Cantón Salcedo, Provincia de Cotopaxi. - Espín Ramírez, Freddy Orlando (2018)
The present project research had as a principal objective to make a register of the religious festivities from the Papahurco community; that is the cultural legacy that is transmitted from generation to generation. Letting to know that this place is full of natural richness as cultural aspects. It is different from other indigenous towns for its customs and own traditions. The study of the intangible heritage was carried out based on the festivities aspects. The first step was carried out as a situational area diagnostic by which it was presented a real local perspective. After that was carried out an inventory control about the intangible heritage (religious festivities), for this, was identified key factors who were the principal source to achieve the collection of the information that got from the field trips and then was carried out the inventory of the community festivities, finally, the data obtained was systemized gotten to make the guide design of religious festivities. To develop this investigation were applied some methodologies, one of them is from Instituto de Patrimonio Cultural (INPC), which consisted in identify key factors to make the interview, where the obtained information was register on the crop sheets (INPC) that is a help instrument to identify the characterization of intangible heritage.